Numerical investigation of forces and acceleration for air-sea unmanned aerial vehicle in transition (2023)
The air-sea UAV is made to be able to fly, change from land to water, and navigate through submerged water. However, as it moves from the air to the water, it experiences a significant impact force. The UAV’s structure and components run the risk of being harmed by this strong impact force. The accelerations and forces involved in the transition process must therefore be understood through quantitative research. The method was created using computational fluid dynamics (CFD), which can manage the process of water entry. The simulation and calculations were carried out using the Fluent software suite from ANSYS Inc. The research examined the UAV’s wing and center bodies independently and separately. 3-D models were used for the analyses of the center body, while 2-D models were used for the wing-body analyses. The transition flow and submerged methods were taken into consideration in obtaining the impact load that a body experiences when transitioning into water. Because it was substantiated using experimental results from prior studies, the transient-time analysis-based transition techniquewas shown to be reliable. The steady-state analysis of the submerged flowmethod can be used to quickly comprehend the pressure and velocity distribution over a body immersed in or entering the water. However, because it fails to account for the water’s initial acceleration upon entry, the steady-state simulation underestimates the drag force. The submerged flow method’s findings indicate that a sharp nose centre body diminishes drag more successfully. The transition method evaluations for the UAV slender body reveal controllable drag and impact forces. Furthermore, the study demonstrates that wedge-shaped leading edges for the wing-body reduce impact but may not be optimal when considering airlift. As a result, this research provides useful data for air-sea UAV structural design and movement conditions.